Impact response of nanoparticle reinforced 3D woven spacer/epoxy composites at cryogenic temperatures. (December 2021) - Yıldırım, Ferhat; Tatar, Ahmet Caner; Eskizeybek, Volkan; Avcı, Ahmet; Aydın, Mustafa
Fiber-reinforced polymer composites serving in harsh conditions must maintain their performance during their entire service. The cryogenic impact is one of the most unpredictable loading types, leading to catastrophic failures of composite structures. This study aims to examine the low-velocity impact (LVI) performance of 3D woven spacer glass-epoxy composite experimentally under cryogenic temperatures. LVI tests were conducted under various temperatures ranging from room temperature (RT) to −196°C. Experimental results reveal that the 3D composites gradually absorbed higher impact energies with decreasing temperature. Besides, the effect of multi-walled carbon nanotube and SiO2 nanofiller reinforcements of the matrix on the impact performance and the damage characteristics were further assessed. Nanofiller modification enhanced the impact resistance up to 30%, especially at RT. However, the nanofiller efficiency declined with decreasing temperature. The apparent damages were visually examined by scanning electron microscopy to address the damage formation. Significant outcomes have been achieved with the nanofiller modification regarding the new usage areas of 3D woven composites.